Analysis of two-dimensional high-energy photoelectron momentum distributions in the single ionization of atoms by intense laser pulses - Chen, Zhangjin; Morishita, Toru; Le, Anh-Thu; Lin, C. D. (My University, 2007)
We analyzed the two-dimensional (2D) electron momentum distributions of high-energy photoelectrons of atoms in an intense laser field using the second-order strong field approximation (SFA2). The SFA2 accounts for the rescattering of the returning electron with the target ion to first order and its validity is established by comparing with results obtained by solving the time-dependent Schrödinger equation for short pulses. By analyzing the SFA2 theory, we confirmed that the yield along the back rescattered ridge in the 2D momentum spectra can be interpreted as due to the elastic scattering in the backward directions by the returning electron wave packet. The characteristics of the extracted electron wave packets for different laser parameters are analyzed, including their dependence on the laser intensity and pulse duration. For long pulses we also studied the wave packets from the first and the later returns.